Iterative thermodynamic modelling—Part 2: Tracing equilibrium relationships between minerals in metamorphic rocks. (20th March 2021) - Lanari, Pierre; Hermann, Jörg
Abstract: Understanding equilibrium relationships between minerals is a fundamental goal of metamorphic petrology, especially for the quantification of metamorphic conditions recorded by crustal rocks. Information on pressure ( P ) and temperature ( T ) can be derived from mineral compositions based on the a priori assumption that frozen‐in assemblages reflect chemical equilibrium at the time of formation. While the stable coexistence of minerals is commonly assessed from a combination of microstructural criteria and interpretation of phase diagrams, there is no robust modelling strategy available so far for the unambiguous recognition of minerals that grew at different conditions. This study uses iterative thermodynamic models and the computer program Bingo‐Antidote to propose a general strategy for assessing the stable coexistence of minerals and therefore for tracing multiple partial equilibrium relationships preserved in metapelites to reconstruct their P – T evolutions. First the principles of this approach are elaborated in a theoretical example. Application to a metapelite from the Western Central Alps reveals a detailed, clockwise P–T path with at least four different equilibration stages including a poorly defined peak pressure at 1–1.1 GPa, 560°C, followed by peak temperatures of 620°C at 0.9 GPa and a late amphibolite stage at 580°C, 0.65 GPa. The investigation of the natural metapelite via iterative thermodynamic models (ITM) allows the observed mineral formation sequence to be combined with a higher accuracy with variable mineral compositions and results in a detailed P–T path. The metastable perseverance of one or more mineral phases can be statistically inferred via ITM. In the investigated metapelite, only 50 vol.% of the rock volume equilibrated at peak temperature conditions of 620°C. In addition, ITM enables a more detailed investigation of partial re‐equilibration by diffusion during subsequent metamorphic stages, showing that prograde garnet growth could have been modified during subsequent 10 Ma of amphibolite facies metamorphism in the Central Alps.